Endovascular revascularization results in IMS III: intracranial ICA and M1 occlusions. (23rd October 2014) - Tomsick, Thomas A; Yeatts, Sharon D; Liebeskind, David S; Carrozzella, Janice; Foster, Lydia; Goyal, Mayank; von Kummer, Ruediger; Hill, Michael D; Demchuk, Andrew M; Jovin, Tudor; Yan, Bernard; Zaidat, Osama O; et al.
Abstract : Background: Interventional Management of Stroke III did not show that combining IV recombinant tissue plasminogen activator (rt-PA) with endovascular therapies (EVTs) is better than IV rt-PA alone. Objective: To report efficacy and safety results for EVT of intracranial internal carotid artery (ICA) and middle cerebral artery trunk (M1) occlusion. Methods: Five revascularization methods for persistent occlusions after IV rt-PA treatment were evaluated for prespecified primary and secondary endpoints, after accounting for differences in key baselines variables using propensity scores. Revascularization was scored using the arterial occlusive lesion (AOL) and the modified Thrombolysis in Cerebral Ischemia (mTICI) scores. Results: EVT of 200 subjects with intracranial ICA or M1 occlusion resulted in 81.5% AOL 2–3 recanalization, in addition to 76% mTICI 2–3 and 42.5% mTICI 2b–3 reperfusion. Adverse events included symptomatic intracranial hemorrhage (SICH) (8.0%), vessel perforations (1.5%), and new emboli (14.9%). EVT techniques used were standard microcatheter n=51; EKOS n=14; Merci n=77; Penumbra n=39; Solitaire n=4; multiple n=15. Good clinical outcome was associated with both TICI 2–3 and TICI 2b–3 reperfusion. Neither modified Rankin scale (mRS) 0–2 (28.5%), nor 90-day mortality (28.5%), nor asymptomatic ICH (36.0%) differed among revascularization methods after propensity score adjustment for subjects with intracranial ICA or M1 occlusion. Conclusions: Good clinical outcome was associated with good reperfusion for ICA and M1 occlusion. No significant differences in efficacy or safety among revascularization methods were demonstrated after adjustment. Lack of high-quality reperfusion, adverse events, and prolonged time to treatment contributed to lower-than-expected mRS 0–2 outcomes and study futility compared with IV rt-PA. Trial registration number: NCT00359424.